Surgical Approaches and Their Outcomes in the Treatment of Cubital Tunnel Syndrome - Carlton, Adam; Khalid, Syed I. (Frontiers in Surgery, 2018)
This review was undertaken in order to provide an updated summary of the current literature on outcomes for various surgical treatments for cubital tunnel syndrome. Studies reporting outcomes for surgical treatment of cubital tunnel syndrome were collected through the PubMed database. Study structure, number of participants/procedures, mean follow-up times, scoring scales, and outcomes were collected according to the type of surgery: open decompression, endoscopic decompression, minimal incision, subcutaneous transposition, intramuscular transposition, and submuscular transposition. Our findings indicate varying but comparable levels of success among all surgical techniques reviewed. Many different scoring scales were utilized, limiting direct quantitative comparison between most studies. While some studies directly compared two or more techniques, there was rarely a statistically significant difference between groups. In comparisons that did reach statistically significant differences, there were others yet that found no difference in comparing the same techniques. None of the techniques in this review has demonstrated universal superiority above all others, but all appear to be effective in the treatment of cubital tunnel syndrome. The only consensus seems to be that transposition is preferred where the ulnar nerve tends to subluxate either on preoperative or intraoperative examination.